Hubungan Kualitas dan Kuantitas Tidur dengan Prestasi Belajar pada Mahasiswa Fakultas Kedokteran - Fenny Fenny; Supriatmo Supriatmo (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2016)
Background: Sleeping is an essential need for every human beings in fulfilling their lives. There are two main components needed to put into consideration; they are sleeping quality and quantity. If the components are being distracted, it will cause impact on memory and concentration system. Consequently, it will cause the decline in academic achievements. The population who are at risk the most will be the collegestudents, especially medical students. Therefore, a research is conducted in order to determine relationship sleep quality and quantity with FK USU students’ academic achievement’s.Method: This research, which is held from March to December 2015, uses analytic methods of case control study. In this study, there are 594 samples that correspond with inclusion and exclusion criterias; then, 150 subjects are being chosen for the case group and 150 subjects are also being chosen for the control group by using a simple random sampling technique. In addition, the research’s datas are collected by using the PSQI and STQ questionnaires, then, they are analyzed by the SPSS computer program. Results: A frequency distribution of the bad sleep quality and the less sleep quantity are the most in the USU’s medical students with the respective figures of 185 respondents (61,7%) and 163 respondents (54,3%). The result of Chi Square analysis also shows that there is a significant relationship with the p value <0,0001 (p≤0,05). Besides, the result of multivariat analysis, which uses logistic regression, shows a final model formula is log p (bad academic achievement) = -1,068+0,570(sleeping quality)+1,303(sleeping quantity). Conclusion: There is a relationship between the sleep quality and quantity with the FK USU students’ academic achievement.